Evaluation of nitrogen requirement and efficiency of rice in the region of Yangtze River Valley based on large-scale field experiments - Ri-huan CONG; Zhi ZHANG; Jian-wei LU; Xiao-kun LI; Tao REN; Wei-ni WANG (Journal of Integrative Agriculture, 2015)
Overestimation of nitrogen (N) uptake requirement is one of the driving forces of the overuse of N fertilization and the low efficiency of N use in China. In this study, we collected data from 1 844 site-years of rice (Oryza sativa L.) under various rotation cropping systems across the Yangtze River Valley. Selected treatments included without (N0 treatment) and with N application (N treatment) which were recommended by local technicians, with a wide grain range of 1.5–11.9 t ha−1. Across the 1 844 site-years, over 96% of the sites showed yield increase (relative yield>105%) with N fertilization, and the increase rates decreased from 78.9 to 16.2% within the lowest range <4.0 to the highest >6.5 t ha−1. To produce one ton of grain, the rice absorbed approximately 17.8 kg N in the N0 treatment and 20.4 kg N in the N treatment. The value of partial factor productivity by N (PFPN) reached a range of 35.2–51.4 kg grain kg−1 with N application under the current recommended N rate. Averaged recovery rate of N (REN) was above 36.0% in yields below 6.0 t ha−1 and lower than 31.7% in those above 6.0 t ha−1. Soil properties only affected yield increments within low rice yield levels (<5.5 t ha−1). There is a poor relationship between N application rates and indigenous nitrogen supply (INS). From these observations and considering the local INS, we concluded there was a great potential for improvement in regional grain yield and N efficiency.